ANALISA PENURUNAN TANAH LUNAK DENGAN BEBERAPA METODE KONSOLIDASI PADA PROYEK JALAN TOL PALINDRA - Puspita, Norma; Capri, Ari (Jurusan Teknik Sipil & Perencanaan Fakultas Teknik Universitas Sriwijaya, 2017)
Based on Daily Traffic Average of Palembang - Inderalaya in 2007, traffic volume of 2 ways of Palembang City for traffic capacity had been reach at 19900 vehicles/2 ways/day. Therefore, in order to decrease traffics jamthen government has built Palembang â Inderalaya Highway (Palindra). According to topography of Palembang City, it has lying on lowland areas with soft soils type which has high compressibility. The objectives of this study are to estimate soft soils settlement with various method of consolidation which are oedometer test, pre-fabricated vertical drain (PVD), and vacuum consolidation method (VCM). The results of this study showed the numbers of settlement of soft soils 1,479 m for 17,24 years in oedometer test, 1,342 m for 105 days in PVD with square pattern, and 1,354 m for 90 days in PVD with triangular pattern. Meanwhile, the numbers of settlement with VCM method have 2,250 m for 105 days with PVD square pattern, and 2,251 m for 90 days with PVD triangular pattern. Based on those results, it can be concluded that VCM triangular pattern more effective than others.